Clinical and Mycobacterium tuberculosis strain characteristics of tuberculosis patients with diabetes mellitus in Changping District, Beijing, China - Xiaolong Cao; Zexuan Song; Ping He; Xinyue Li; Nan Lei; Qian Sun; Xue Wang; Ruida Xing; Bing Zhao; Xinyu Yang; Zhiguo Zhang; Yanlin Zhao (BMC Infectious Diseases)
Abstract Background Diabetes mellitus (DM) is a major risk factor for tuberculosis (TB), However, limited research exists on their clinical and strain characteristics. This study aims to investigate the correlation between these factors in TB-DM patients in Changping District.  Methods Whole genome sequencing (WGS) and drug susceptibility tests (DST) were performed on culture-positive strains. Spearman correlation analysis was used to examine risk factors and the correlation between lineage, cavities, and hemoptysis in the TB-DM population. The specificity, sensitivity, and confidence intervals for predicting phenotypic drug resistance based on genotypic resistance were calculated. Results Among the 3924 TB patients, 292 had DM, showing a doubling in the proportion of TB patients with DM over seven years. Among the 144 etiologically positive TB-DM cases treated at the Changping Institute for Tuberculosis Prevention and Treatment, 75% (108/144) of the patients exhibited tuberculosis lesions that formed cavities and 12.5% (18/144) with hemoptysis. A statistically significant difference in cavity formation across different age groups was observed (r = -0.198, P < 0.05). Out of the 144 etiologically positive patients, WGS successfully revived 73 MTB strains, with Lineage 2 being predominant. No statistical difference was found between lineages and the presence of cavities or hemoptysis. The DST results showed the highest resistance rates to isoniazid and streptomycin, both at 8.2% (6/73), with approximately one-quarter of the strains resistant to at least one anti-TB drug, and about half (47.1%, 8/17) resistant to first-line drugs. The study demonstrated good specificity but suboptimal sensitivity in predicting phenotypic drug resistance based on genotypic resistance. Conclusions The rising incidence of diabetes in tuberculosis patients within Changping District has intensified the spread of TB, with these patients demonstrating severe illness and high drug resistance. This study aims to develop targeted prevention and management strategies, offering crucial guidance for treating co-infections of TB and DM and controlling disease spread.